Eksplorasi Nilai-nilai Kesetaraan dalam Pendidikan Pesantren Mu’ādalah - Mufiqur Rahman; Maskuri Bakri; Hasan Busri; Zainullah Zainullah; Roro Kurnia Nofita Rahmawati (UIN Sunan Ampel Surabaya, 2020)
One of the values ​​of Islamic moderation is equality. Equality in education is very important to ensure a just education process (equity) and equality. The Mu'ādalah pesantren is an exclusive educational unit, with an education system that is autonomous, independent and different from schools, madrasahs or other types of pesantren. This study aims to explore the values ​​and practices of equality in Mu'ādalah pesantren inclusively. With an ethnographic research, Pesantren Al-Amien Prenduan Sumenep was chosen as the research locus. This research found that, Al-Amien pesantren is not only an institutionally equal Mu'ādalah Islamic Boarding School, but also has substance and practical equality itself. Spiritual values, integration of Islam and Indonesianness, and the implementation of local pesantren culture in institutional practices justify the essence of the equality of mu'ādalah pesantren vis-a-vis other educational institutions.